2014
DOI: 10.1371/journal.pone.0109108
|View full text |Cite
|
Sign up to set email alerts
|

The Structure of an LIM-Only Protein 4 (LMO4) and Deformed Epidermal Autoregulatory Factor-1 (DEAF1) Complex Reveals a Common Mode of Binding to LMO4

Abstract: LIM-domain only protein 4 (LMO4) is a widely expressed protein with important roles in embryonic development and breast cancer. It has been reported to bind many partners, including the transcription factor Deformed epidermal autoregulatory factor-1 (DEAF1), with which LMO4 shares many biological parallels. We used yeast two-hybrid assays to show that DEAF1 binds both LIM domains of LMO4 and that DEAF1 binds the same face on LMO4 as two other LMO4-binding partners, namely LIM domain binding protein 1 (LDB1) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 79 publications
1
14
0
Order By: Relevance
“…Size exclusion chromatography coupled to multi-angle laser light scattering was carried out as described previously 40 . Briefly, 250 μL (corresponding to 250 μg) of purified protein in MALS buffer (20 mM Tris pH 7, 100 mM NaCl, 1 mM EDTA, with or without 1 mM TCEP) was injected onto a Superose 12 10/30 analytical size exclusion column mounted to an AKTA chromatography system in tandem with a MALS detector.…”
Section: Methodsmentioning
confidence: 99%
“…Size exclusion chromatography coupled to multi-angle laser light scattering was carried out as described previously 40 . Briefly, 250 μL (corresponding to 250 μg) of purified protein in MALS buffer (20 mM Tris pH 7, 100 mM NaCl, 1 mM EDTA, with or without 1 mM TCEP) was injected onto a Superose 12 10/30 analytical size exclusion column mounted to an AKTA chromatography system in tandem with a MALS detector.…”
Section: Methodsmentioning
confidence: 99%
“…which also interact with the PI3K/mTOR pathway [55]. Yeast two-hybrid assays demonstrated that DEAF1 and LDB1 binds with LMO4 through LIM domains [56]. LDB1 interacts with CHD8, which is regulated by CTNNB1, a key downstream gene of GSK3B.…”
Section: Discussionmentioning
confidence: 99%
“…2J). Previous studies suggest that binding regions for LMO4 frequently contain hydrophobic amino acids and particularly leucine (L) and valine (V) are crucial for the binding interface (34). Jacob contains a leucine-rich stretch of amino acids between 173-228 aa (Fig.…”
Section: Jacob Is a Direct Binding Partner Of Crebmentioning
confidence: 99%